Enamel matrix derivative as an adjunct to minimally invasive non‐surgical treatment of intrabony defects: A randomized clinical trial. (9th November 2021) - Anoixiadou, Styliani; Parashis, Andreas; Vouros, Ioannis
Abstract: Aim: To compare the efficacy of minimally invasive non‐surgical technique (MINST) with or without enamel matrix derivative (EMD) in the treatment of intrabony defects ≤7 mm. Materials and methods: Thirty‐six patients were randomly assigned to the two groups. The control group received MINST, while the experimental MINST+EMD. Clinical measurements were recorded at baseline and at 6 and 12 months, and radiographic measurements were made at baseline and 12 months. Results: All subjects completed the study, 18 in each group. Significant improvements were observed in both groups at 12 months ( p  < .001) with no differences in mean PD reduction (4.0 ± 1.4 vs. 4.2 ± 1.7 mm), CAL gain (3.5 ± 1.4 vs. 3.4 ± 1.6 mm), and defect resolution (1.9 ± 1.1 vs. 1.8 ± 0.9 mm) for the MINST and the MINST+EMD groups, respectively ( p  > .05). A trend for greater pocket closure (PD ≤4 mm and no BoP) was achieved with the application of EMD (77.8% vs. 55.6% sites), particularly for sites with baseline PD ≤8 mm (92.3% vs. 69.2% sites), accompanied by an increased number of successful composite outcome results (61.1% vs. 44.4% sites). Conclusions: MINST demonstrates significant improvements 12 months after treatment of intrabony defects ≤7 mm. The additional application of EMD does not further improve the mean clinical or radiographic outcomes. This study is registered in ClinicalTrials.gov (NCT03622255).